Content of the cyanogenic glucoside amygdalin in almond seeds related to the bitterness genotype (2012)
Almond kernels can be sweet, slightly bitter or bitter. Bitterness in almond (Prunus dulcis Mill.) and other Prunus species is related to the content of the cyanogenic diglucoside amygdalin. When an almond containing amygdalin is chopped, glucose, benzaldehyde (bitter flavor) and hydrogen cyanide (which is toxic) are released. This two-year-study with 29 different almond cultivars for bitterness was carried out in order to relate the concentration of amygdalin in the kernel with the phenotype (sweet, slightly bitter or bitter) and the genotype (homozygous: sweet or bitter or heterozygous: sweet or slightly bitter) with an easy analytical test. Results showed that there was a clear difference in the amount of amygdalin between bitter and non-bitter cultivars. However, the content of amygdalin did not differentiate the other genotypes, since similar amounts of amygdalin can be found in the two different genotypes with the same phenotype.